Pengaruh Pemahaman Regulasi, Digitalisasi dan Program Pengungkapan Sukarela Terhadap Tingkat Kepatuhan Wajib Pajak Orang Pribadi - Anggie Novita; Diana Frederica (Juara: Jurnal Riset Akuntansi, 2023)
The purpose of this study was to examine and analyze the effect of understanding tax regulations, digitization, and the Voluntary Disclosure Program on individual taxpayer compliance. The data collection method uses primary data by distributing e-questionnaires based on each indicator and processed using data processing software, namely Smart PLS 4. Variable measurement in this study uses an ordinal scale and simple random sampling and the sample taken from this study is taxpayers who have NPWP and registered at KPP DKI Jakarta with a total sample of 125 respondents. The results of this study indicate that: (1) understanding of regulation has a significant positive effect on taxpayer compliance (2) digitization has a significant positive effect on taxpayer compliance (3) Voluntary Disclosure Program has no positive significant effect on taxpayer compliance. For future researchers as a consideration of the strengths and weaknesses that might exist in this study if the next researcher wants to do similar research first. For Directorate General of Taxes, this research is expected to be able to make a good contribution and can be used as reference material to make and decide on innovative ideas to increase taxpayer compliance.